Evaluation of silage diets offered to reindeer calves intended for slaughter. I. Feeding of silage and barley from September to March - Nilsson, Anna; Olsson, Ingemar; Lingvall, Per (Rangifer, 1996)
An experiment involving 75 male reindeer calves (mean initial live weight 39.6 kg, SD=3.7) intended for slaughter was undertaken to study the effect of proporrion of barley to silage in the diets on animal performance. The calves were alloted to five groups including one group slaughtered at the start of the experiment in September. The remaining groups were offered diets containing either, 30% (LB), or 60% (HB) rolled barley, based on the dry matter (DM) content, until slaughter in November (LB and HB) or in March (HB). The silage (43% DM) was made from the primary growth of a predominantly grass sward preserved as plastic-wrapped big bales. Small amounts of lichens were mixed with the rations during rhe first two weeks of the experiment and the calves adapted well to the experimental diets. However, health problems and deaths occurred on borh rarions after five weeks of feeding. Since the animals fed the LB diet lost live weight and condition the experimental feeding of these calves were interrupted at the slaughter in November. Calves fed the LB diet had significantly lower daily DM intake (P<0.01). They also had lower live weighr gain (not significant), greater losses of carcass weight and fat in the abdominal cavity relative to those offered the HB diet. During the second period of the study the remaining animals offered the HB diet showed no signs of ill-health and increased live weight, carcass weighr, and fat in the abdominal cavity. The results of the presenr experiment indicate that when silage of the investigated quality is fed to reindeer calves rhe proportion of silage should not exceed 40% of the DM.